Pengendalian Penyakit Rabies melalui Media Komunikasi, Informasi, dan Edukasi kepada Masyarakat di Kota Padang - Shila Rahmafia Putri; Agus Setiyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Rabies is a zoonotic disease caused by a virus belonging to the Lyssa virus and the family of Rhabdoviridae. Rabies becomes an endemic to 24 of 34 province in Indonesia, including West Sumatera. This condition makes rabies becomes a priority for the Indonesian goverment. Another way to control the spread of this disease beside a vaccination is through a counseling to the community with a media of communication, information, and education (CIE) about rabies. The CIE about rabies activity aims to educate the community about the dangers of rabies and the measures that could be taken if someone is being bitten by a rabies infectious animal. The CIE about rabies activity in Padang are carried out through two-way communication with posters, rabies games boards, and zoonotic knowledge books. This activity was attended by 1471 participants from various professions in the city of Padang. Through this activity, the community got information about the dangers of rabies, the characteristics of animals that infected with rabies, how rabies is transmited, and the steps for handling if someone is bitten by a rabies infectious animal. Keywords: CIE, Padang city, rabies